Hermansky-Pudlak syndrome - Prabodh Panchadhyayee; Arnab Saha; Kaushik Saha; Rupam Kumar Ta; Pratik Barma (Wolters Kluwer Medknow Publications, 2014)
Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder characterized by oculocutaneous albinism, bleeding diathesis and lysosomal deposition of ceroid lipofuscin pigment. Interstitial lung disease may also accompany with the disease. Cases are mainly found among individuals with Puerto Rican ancestry. It develops due to defects in the biogenesis and/or function of lysosome-related organelles essential to membrane and protein trafficking. A 30-year-old Hindu male patient with oculocutaneous albinism, strabismus, nystagmus and severe dimness of vision presented to us for severe shortness of breath. Subsequent investigations revealed he had HPS with an advanced stage of pulmonary fibrosis.